2019
DOI: 10.1007/s12070-019-01608-y
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Laryngoplasty in Pediatric Population with Subglottic Stenosis: 5 Years Experience in King Abdulaziz University Hospital a Tertiary Center

Abstract: We reviewed our experience with balloon laryngoplasty (BLP) as a primary management of SGS in a tertiary care center in Saudi Arabia. In this review, a total of 147 patients who underwent Laryngobronchoscopy were reviewed. Only 10 pediatric patients diagnosed with SGS who underwent BLP as primary treatment in the period from January 2012 to December 2017 were included. After obtaining ethical approval, included patients' charts were reviewed. Adult patients and those with airway anomalies other than SGS were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…While used in grade III, as a primary step to improve breathing for a short time 2-4 weeks then underwent to open procedure. This agreement with previous studies was reported that dilatation of grades I, II, gives a high success rate [16,17]. More concerns were raised in another recent comparative study by Mareschal etal (2014) [18] who stated that there is a poor definition of the safety profile for balloon dilatation.…”
Section: Resultssupporting
confidence: 88%
“…While used in grade III, as a primary step to improve breathing for a short time 2-4 weeks then underwent to open procedure. This agreement with previous studies was reported that dilatation of grades I, II, gives a high success rate [16,17]. More concerns were raised in another recent comparative study by Mareschal etal (2014) [18] who stated that there is a poor definition of the safety profile for balloon dilatation.…”
Section: Resultssupporting
confidence: 88%